Tacit contributions and roles of senior researchers: Experiences of a multinational company - Walter Pérez Villa; Amaya Pérez-Ezcurdia; Miguel Angel Vigil Berrocal (Administrative Sciences, 2022)
One of the concerns of innovation-dependent organisations is that the gradual increase in the average age of their employees might affect their creativity and innovation rates, leading to losses in competitiveness. The purpose of this paper was to deepen the identification and understanding of the contributions done by senior researchers within a private organisation. This study was based on field qualitative research on a multinational company. Interviews were performed were senior researchers and the transcripts were analysed with a qualitative data analysis (QDA) software to organise, analyse and find insights in unstructured or qualitative data. Analysis was performed using axial coding, which relates data together to reveal codes and categories from participants' voices within the collected data. The points of view of senior researchers were explicitly sought and the findings indicated that these veteran professionals can be more valuable for their contributions as experienced workers than for their scientific productivity at the individual level, without disregarding it. Senior researchers have acquired tacit skills linked to their experience, such as a holistic view of the issues and efficient work methodologies. Therefore, they develop formal or informal roles over time related to advice and knowledge transfer. Consequently, it was found that their tacit contributions and roles increase the intellectual capital of the organisation. This paper helps in understanding the contributions made by senior researchers within a private organisation. No other reviews have sought to obtain such information on this specific sector.
Keywords: 350; age management; ageism; industrial researchers; intangible assets; intellectual capital; knowledge transfer; patenting; senior researcher motivation; senior researcher perspective; senior researcher role; tacit contributions